(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2019)
Assignment problem is a type of optimization problem which deals with allocation of different resources to different activities on one-to-one basis. It has a lot of relevance in practical life as many real world problems are formulated in the form of an assignment problem. In this research paper, a different approach (other than the existing methods in literature) for solving an assignment problem has been introduced along with the algorithm and numerical example.